Practices of Dynamic Order. Issue 2 (16th May 2018) - Jabko, Nicolas; Sheingate, Adam
Abstract : In accounting for the endurance of dysfunctional institutions, scholars often highlight the importance of path dependence or incremental change. Yet this fails to capture the creativity that actors deploy to reproduce order, particularly in times of crisis. We propose the concept of dynamic order, rooted in pragmatist theory, as an alternative way to think about institutional durability. Powerful actors reproduce order through creative adjustments to rules and routines that channel action into predictable and controllable behavior. We illustrate this dynamic with examples from the European Union and the United States. In response to the crisis of the Eurozone, EU and state officials invented new procedures that strengthened European governance at the very moment many questioned whether the euro could survive. Likewise, in the United States, public officials responded to social movements and street protests against racism and police brutality by creatively channeling these grievances into judicial proceedings and procedures controlled by the state. By focusing on how elite actors regenerate order in times of crises, our analysis enhances the conceptual toolkit currently available to the scholars of institutions.